The Relationship between the Intensity of Solar Radiation and the Output Photovoltaic Using Multiple Linier Regression Methods in North Sumatera - Dewi Sholeha; Managam Simamora, Antonius; Joslen Sinaga; Faisal, Ahmad (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2025)
In Indonesia, measurements of solar radiation intensity are mostly carried out at climatology stations. The relationship between radiation intensity and solar radiation duration as well as other weather parameters has not been thoroughly identified, so whether radiation intensity will influence each other or not at all on radiation duration and other weather parameters. This study aims to analyze the correlation between the intensity of solar radiation and weather factors which include the length of sunlight, average humidity, rainfall, average wind speed, and average temperature. To analyze the correlation of this study using multiple linear regression method with the help of SPSS 22 software and to calculate the potential of this study using solar panels with an efficiency of 17.72%. From the regression results, it was found that all the variables tested simultaneously had an effect, but partially only one variable had a significant effect, namely the length of solar irradiation on the intensity of solar radiation also of the five variables only rainfall which had an inverse relationship to the intensity of solar radiation. Of all the variables tested, it can explain the solar radiation intensity variable by 93.6%. However, partially only one variable has a significant effect on the intensity of solar radiation, namely the duration of solar radiation and also of the five variables only rainfall which has an inverse relationship to the intensity of solar radiation.